FORMATION OF THE RATIONAL FUEL AND ENERGY BALANCE OF THE STATE: A SCIENTIFIC AND EMPIRICAL APPROACH - SHCHUROV, IGOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
One of the main criteria for the effectiveness of the national economy functioning is energy security, as an important element of national security. Energy supply is one of the main problems of the national economy. The sustainable development of the country depends on the solution of this problem, which affects the effective use of economic, ecological, social and other resources. The article focuses on the conditions for the formation of energy security, in particular, micro-, meso- and macro-competition; a scientific and empirical approach to the formation of a rational fuel and energy balance of the state was developed; the basic concepts of energy security of the country are given; a list of steps for the study of energy security in the country was formed. By conducting an analysis of threats to energy security, threats that directly affect the energy complex of Ukraine are singled out. The factors of the imperfection of the management system in threats to the country’s energy security are schematically depicted and the process of complicating the formation of strategic and tactical directions of the country’s prospective energy balance is proven.